Psychological Assumptions and Early Maladaptive Schemas in People with Traumatic Experience - V.A. Stepashkina; N.R. Suleymanova (Консультативная психология и психотерапия, 2023)
Introduction. This article describes the mutual influence of the phenomena of psychological assumptions, early maladaptive schemas (EMS), traumatic experience. The significance of this study is based to the need for psychologists to carry out practical work with the complexity and severity of the consequences of a person’s traumatic experience, specifics of beliefs and EMS. Purpose: To study psychological assumptions and EMS, which are formed from childhood and increase the impact on the personality in connection with the traumatic experience reducing the adaptive capacity of the individual. Methods. The article presents the results of a study of 45 people: females (31 participants) and males (14 participants), at the age 24–40 years old (M = 33,9; SD = 5). The specificity of the manifestation of differences in psychological assumptions and EMS in individuals with high and low rates of trauma is described. The following methods were used: the questionnaire of traumatic situations (Life Experience Questionnaire – LEQ), an adaptation of the WAS (World Assumptions Scale), the questionnaire for an adapted version of determining early maladaptive schemes by Jeffrey E. Young. Results and conclusions. Differences in groups with high and low rates of traumatism were identified: the individuals who survived a traumatic experience are characterized by a higher level of EMS «Abandonment/Instability», «Social Isolation», «Vulnerability» and «Negativity/Pessimism»; persons with a low level of traumatism are characterized by the manifestation of conviction in the «goodwill of the world». A relationship was found between the image of the «Self», the basic belief about luck, a high level of trauma and EMS in people who had a traumatic experience.